Multiband variability of the TeV blazar PG 1553+113 with XMM–Newton. Issue 1 (22nd June 2021) - Dhiman, Vinit; Gupta, Alok C; Gaur, Haritma; Wiita, Paul J
ABSTRACT: We present variability analyses of twenty pointed XMM–Newton observations of the high energy peaked TeV blazar PG 1553+113 taken during 2010–2018. We found intraday variability in the total X-ray energy range (0.3–10 keV) in 16 out of 19 light curves or a duty cycle of ∼84 per cent. A discrete correlation function analysis of the intraday light curves in the soft and hard X-ray bands peaks on zero lag, showing that the emission in hard and soft bands are co-spatial and emitted from the same population of leptons. Red-noise dominates the power spectral density (PSD) of all the LCs, although the PSDs have a range of spectral slopes from −2.36 to −0.14. On longer time-scales, the optical and UV variability patterns look almost identical and well correlated, as are the soft and hard X-ray bands, but the optical/UV variations are not correlated to those in the X-ray band, indicating that the optical/UV and X-ray emissions are emitted by two different populations of leptons. We briefly discuss physical mechanisms that may be capable of explaining the observed flux and spectral variability of PG 1553+113 on these diverse time-scales.